(untitled) (Architecture Image Studies, 2025)
Sustainability has become an increasingly important aspect in the textile industry, given the significant environmental impacts of textile production, such as water pollution, greenhouse gas emissions, and textile waste. In an effort to reduce these negative impacts, sustainability has become a major focus for many textile companies to ensure a more environmentally friendly and sustainable future. This study aims to foster green entrepreneurship and innovation in the textile industry in Palembang. Focusing on green entrepreneurial orientation and spiritual intelligence, this study aims to improve sustainability performance through the implementation of green innovation that includes environmentally friendly products and processes. This study uses Partial Least Squares (PLS) and Support Vector Regression (SVR) analysis to reduce data dimensions and build prediction models. SVR is used to create a more accurate prediction model by taking into account pertinent research factors, whereas PLS is used to assess the connection between latent variables and their indicators. The main findings indicate that green entrepreneurial orientation and spiritual intelligence have a significant influence on green innovation and sustainability performance. Green innovation is a key mediator in enhancing sustainability performance, as demonstrated by the usefulness of PLS and SVR in revealing the intricate interactions between these factors. Furthermore, the study’s findings indicate that green innovation and sustainability performance are not significantly impacted by green entrepreneurial self-efficacy. Green entrepreneurial orientation and spiritual intelligence play an important role in driving green innovation and sustainability performance. Green innovation is proven to be a key element that links various internal factors with sustainability performance outcomes. This study provides important practical implications for textile SMEs in Palembang in improving their competitiveness and sustainability, as well as providing valuable insights for policymakers in designing programs that support green entrepreneurship.